Management of distal radius fracture: A comparison of actual and theoretical treatments. (December 2018) - Xie, Linzhen; Chen, Chunhui; Yu, Xianbin; Hu, Wei; Chen, Hua; Sun, Liaojun
Abstract: Purpose: The objective of this study was to explore whether there were any differences between the theoretical operative treatment of distal radius fractures according to AAOS guideline on basis of measurement of radiographs and the treatment they actually received in our institution. Methods: From April 2015 to February 2018, a total of 693 patients with 697 fresh close adult distal radius fractures were evaluated retrospectively. Fractures were respectively grouped into categories by AAOS criterion and actually treatment. After gleaning demographic information and measuring radiographic items, all results were put into a database. Single factors analysis, Chi-square test and further logistic regression analysis were performed to determine correlations between actual and theoretical treatments. Results: In all 240 fractures fulfilled at least one AAOS criterion for surgery, only 61 fractures actually received operation. And in the conservative group recommended by AAOS, 52 of 457 fractures actually were proceeded with surgery. There were slight correlation between AAOS guideline and actually operation (Phi = 0.181). From multivariable logistic regression analysis, Only one of three AAOS criterion was proved probable indicator of clinic treatment. Three factors, namely age, intra-articular step-off as well as with other fractures, were proved probable actually surgery indications (P < 0.05). Conclusions: AAOS surgery criteria of distal radius fractures were partially instructive, but not so precise predictors for actually operation. In the clinic, the choice of operative treatment correlated with multiple factors. Highlights: A comparison of actual and theoretical treatments of distal radius fractures. 697 fractures were included. The indicators that may affect choice of management were analyzed by univariate analysis and logistic regression analysis.